Comparison of Diagnostic Performances of ATA Guidelines, ACR-TIRADS, and EU-TIRADS and Modified K-TIRADS: A Single Center Study of 4238 Thyroid Nodules - Özdemir, Mustafa; Türk, Gamze; Bilgili, Mustafa; Akay, Ebru; Koç, Ali (Experimental and Clinical Endocrinology & Diabetes, 2025)
Several ultrasound-based risk stratification systems (RSSs) have been developed and introduced into clinical practice for managing thyroid nodules. However, there are essential differences among these systems. This study aimed to determine and compare the category-based diagnostic performance of four ultrasound-based risk stratification systems in the detection of thyroid cancer: ACR-TIRADS, ATA, K-TIRADS, and EU-TIRADS.This study included 4238 nodules sampled by fine-needle aspiration biopsy between January 2018 and December 2021. Nodules were classified according to ultrasound imaging features and correlated with biopsy results. The diagnostic success of the risk stratification systems was evaluated and compared.Of the 4238 nodules, 3861 (91.1%) were benign and 376 (8.9%) were malignant. Malignancy was significantly higher in hypoechoic and marked hypoechoic nodules (p=0.001), and solid nodules (p=0.002). For detection of malignancy, areas under the receiving operator characteristics curves were 0.862, 0.850, 0.842, and 0.835 for 2017 ACR-TIRADS, EU-TIRADS, for K-TIRADS, and 2015 American Thyroid Association guidelines, respectively. EU-TIRADS showed the highest sensitivity (91%), whereas ACR-TIRADS had the highest specificity (87%). Compared to other risk stratification systems, ACR-TIRADS resulted in significantly fewer unnecessary biopsies (p=0.009). All RSSs show high diagnostic accuracy and have their own advantages and disadvantages. When selecting an appropriate RSS, the population, the prevalence of the disease, and gender distribution should be considered.
Keywords: thyroid nodules; fine-needle aspiration; ultrasound; TIRADS classification